Jigsaw and Student Team Achievement Division (STAD) Techniques in Teaching English Reading - Caesar Astri Perwitasari; Ag. Bambang Setiyadi; Gede Eka Putrawan (Universitas Lampung, 2017)
The objectives of the research were aimed at finding out the responses the students had during the implementation of Jigsaw technique and Student Team Achievement Division (STAD). This research was done through a qualitative design. The population of this research was the second grade students at SMPN 1 Abung Surakarta. The result showed that there were some obstacles found during the implementation of the Jigsaw and STAD Technique as follows: (1) limited vocabulary knowledge; (2) difficulty level of the text (readability); (3) noisy class situation; (4) no students background knowledge; (5) hesitancy to express opinions; (6) class dominated by the smart students. The results showed that there were obstacles that students faced during teaching, and learning reading comprehension in the class using Jigsaw, and STAD Technique.Keywords: Jigsaw Technique, reading comprehension, STAD Technique DOI: http://dx.doi.org/10.23960/aksara/v18i2.pp169-177